2023
DOI: 10.3390/antiox12040911
|View full text |Cite
|
Sign up to set email alerts
|

Recent Trends on Mitigative Effect of Probiotics on Oxidative-Stress-Induced Gut Dysfunction in Broilers under Necrotic Enteritis Challenge: A Review

Abstract: Gut health includes normal intestinal physiology, complete intestinal epithelial barrier, efficient immune response, sustained inflammatory balance, healthy microbiota, high nutrient absorption efficiency, nutrient metabolism, and energy balance. One of the diseases that causes severe economic losses to farmers is necrotic enteritis, which occurs primarily in the gut and is associated with high mortality rate. Necrotic enteritis (NE) primarily damages the intestinal mucosa, thereby inducing intestinal inflamma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 192 publications
(403 reference statements)
0
5
0
Order By: Relevance
“…Additionally, the composition and quantity of gut microbes is a key factor in maintaining integrity of the intestinal structure, promoting maturation of the immune system, and modulating host immune responses ( Obianwuna et al., 2023 ). Studies indicated that intestinal flora would be shaped by C. perfringens challenge, resulting in a reduction of beneficial bacteria and an increase of pathogenic bacteria ( Lu et al., 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the composition and quantity of gut microbes is a key factor in maintaining integrity of the intestinal structure, promoting maturation of the immune system, and modulating host immune responses ( Obianwuna et al., 2023 ). Studies indicated that intestinal flora would be shaped by C. perfringens challenge, resulting in a reduction of beneficial bacteria and an increase of pathogenic bacteria ( Lu et al., 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous psychological (an emotion and/or mental overstimulation) and/or physical (environmental conditions) stressors reduce gut microbiota diversity and/or alter microbiome composition by (1) disrupting the community stability of commensal bacterial populations, often accompanied by reduced beneficial bacteria and increased pathogens (causing a chronic low-grade inflammation); (2) increasing the survival translocation of pathogens and releasing virulence factors; (3) disrupting absorption of nutrients and minerals (metabolic disorders); (4) disrupting microbial neuroendocrine functions (alterations in synthesis of several signaling molecules and neurochemicals including 5-HT in the GIT); (5) disrupting the gut epithelial barrier, thereby increasing intestinal permeability and releasing certain bacteria, bacterial antigens, and metabolites (leaky gut), resulting in both intestinal and systemic immune reactions; and (6) damaging epithelial cells, producing free radicals and reducing antioxidant capacity (oxidative stress) [ 142 , 143 , 144 ]. These changes in the gut microbiota with a chronic low-grade inflammation profoundly influence host health and behavioral homeostasis via the MGB and MGI axes [ 58 , 145 ].…”
Section: Cecal Microbiota Transplantation Social Stress and Injurious...mentioning
confidence: 99%
“…(5) disrupting the gut epithelial barrier, thereby increasing intestinal permeability and releasing certain bacteria, bacterial antigens, and metabolites (leaky gut), resulting in both intestinal and systemic immune reactions; and (6) damaging epithelial cells, producing free radicals and reducing antioxidant capacity (oxidative stress) [142][143][144]. These changes in the gut microbiota with a chronic low-grade inflammation profoundly influence host health and behavioral homeostasis via the MGB and MGI axes [58,145].…”
Section: Stress and Gut Microbiotamentioning
confidence: 99%
“…Gut permeability changes also allow the translocation of immunogenic bacteria, endotoxins, and antigens that can lead to chronic immune activation. The suppressed immunity and inflammation from microbial imbalance and gut barrier disruption likely underlie much of the reduced performance observed after removing antibiotic growth promoters (47,48).…”
Section: Impacts Of Antibiotic Growth Promoter Restrictions On Poultr...mentioning
confidence: 99%